Where truth lies : digital culture and documentary media after 9/11 (2019)
In 2016, when real-estate heir and reality-television figure Donald Trump was unexpectedly elected president of the United States, media were to blame. Mainstream media (the news) had missed a silent majority of working-class voters in their focus on the opinions and preferences of coastal elites. Marginal media (fake news) had manufactured lies and manipulated low-information voters. Quantitative media (data) had used faulty models and outdated polling techniques to predict the outcome. Social media (Twitter) had been weaponized to manipulate the news cycle and bully and intimidate critics. Deleted, hacked, and ultimately leaked media (e-mails) had cast doubt on an otherwise trustworthy candidate. Even the electoral college—a sort of political medium designed to transmit and translate the will of the voters into the constitutional form of elected office—had failed to accurately reflect and communicate the choice of a majority of voters. While the full impact of Trump’s election will take many years to play out, the initial surprise—some might say shock—it generated reveals a great deal about the relationship between politics and media (or politics as media) in contemporary American culture. The first revelation is the vast quantity and heterogeneity of information sources. Data, images, private messages, public proclamations, professional insiders, and renegade outsiders were all deemed credible in some context for some audience. Media have perhaps never before been so numerous or so diverse. The second point is that in spite of this variety, all of these forms are still considered nonfiction media. For the audiences they attract, they engender a degree of faith in their ability to accurately reflect reality. Simply put, they can tell the truth. They are, in other words, documentary media. And finally, of course, they were all wrong.